ANALISIS MANAJEMEN OPERASIONAL PT INDOFOOD SUKSES MAKMUR TBK (ICBP) - Cuandra, Fendy -; Karimah, Zulfiniar Nur; Rahmah, Ayu Fauzia; Kennedi, Efriza Shahara; Hendro, Hendro - (Makro Jurnal Manajemen Dan Kewirausahaan, 2023)
Operational management of PT. Indofood Sukses Makmur Tbk (ICBP) in terms of managing quality, human resource management, supply chain management as well as the implementation of MRP and ERP are the subject of discussion to find out operational problems and strategies for dealing with them before, during and after the COVID 19 pandemic. The research was conducted using qualitative methods and using secondary data. The results of the research show that the strategies that can be pursued to solve these problems are by carrying out audits, using Six Sigma to manage quality, balancing the latest conditions in the new normal period and maintaining productivity and efficiency of work targets in human resources, using E SCM and Big Data in supply chain management, and continue to utilize the use of ERP in integrating all of the company's